THE POWERFUL OF ENGLISH LEARNING STRATEGIES APPLIED BY STUDENTS IN TEFL - ardayati ardayati; maria ramasari (STKIP PGRI Lubuklinggau, 2021)
This research was to identify students’s English learning strategies. Seventh grade students in VII.3 at SMP Negeri B.Srikaton was the subject. Method in this research was survey research design. The researcher used questionnaire of Strategy Inventory for language learning (SILL) by Rebecca L. Oxford and interview. In analyzing the data, researcher used four steps; they were identification, classification, description and conclusion. Based on the result of data analysis, it was found there were 6 kinds English learning strategies used by students. The strategies were memory strategies, cognitive strategies, compensation strategies, metacognitive strategies, affective strategies and social strategies. The most dominant strategy in English learning strategies was metacognitive strategy with the total 9 students. The second 8 students was cognitive strategy. The third, affective strategies 8 students. The next, 7 students was memory strategies. Then, social strategy with 2 students and the least, compensation strategy only had 2 students